Strategi Jurnalis Investigasi dalam Penyajian Berita Pemberantasan Kejahatan Narkotika di Badan Narkotika Nasional Republik Indonesia - Tafuzi Fauriana; Leonard Dharmawan (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study aims to analyze the strategies employed by investigative journalists in presenting news on narcotics crime eradication by the National Narcotics Agency of the Republic of Indonesia (BNN RI). A qualitative descriptive approach was applied using Teun A. Van Dijk’s discourse analysis model, encompassing textual structure, social cognition, and sociocultural context. Data were collected through literature review, observation, documentation of BNN’s official news, and in-depth interviews with BNN-affiliated journalists. The primary object analyzed is the news article titled “Proving Commitment to Eradicate Drugs: BNN Seizes 1.2 Tons of Narcotics Evidence” published on March 3, 2025. The findings indicate that the news is constructed using narrative strategies that emphasize professionalism, operational success, and nationalistic sentiment. Declarative sentence structures, technical and quantitative lexicon, and war-like metaphors are employed to reinforce the image of BNN as a firm, collaborative, and committed institution in combating narcotics. The analysis also reveals efforts to strengthen national discourse through collective calls to action and symbolic narratives such as “Indonesia Bersinar” (Indonesia Free from Drugs). These findings suggest that investigative journalism within government institutions not only serves to disseminate information but also functions as a tool for institutional legitimacy and public education in addressing criminal issues.